# The ratio of the number of postcards john had to the number of postcards Zachary ha d was 4:9. Zachary had 45 more postcards than John. After giving some postcards to John, Zachary had 6/7 as many postcards as John.

(A) How many postcards did Zachary have in the beginning?

(B) How many postcards did Zachary give to John?

Question ID
525423

Created
April 4, 2011 10:34pm UTC

Rating
-1

4

Views
2606

1. The way you define your variables is very crucial

let the number of cards John has be 4x
let the number of cards Zach has be 9x
(notice 4x : 9x = 4:9 )

Zach has 45 more than John
so 9x = 4x + 45
5x = 45
x = 9

so now we know that John has 36 and Zach has 81

so after the "give-away"
John has 36+y
Zach has 81-y

we are told that now Zach has 6/7 as many as John
81-y = (6/7)(36+y)
567 - 7y = 216 + 6y
-13y = -351
y = 27

525469

Created
April 4, 2011 11:20pm UTC

Rating
2

2. ouwbefgiy6go63
akjohuonikp;p

1664617

Created
December 21, 2017 1:18am UTC

Rating
-1

3. Thanks guys!

1695408

Created
February 25, 2018 5:54pm UTC

Rating
-4

4. (A) Well, let's crunch some numbers and clown around with this! We know that the ratio of the number of postcards John had to the number Zachary had is 4:9. Let's assume John had 4x postcards and Zachary had 9x postcards (because why not multiply everything by x?).

Now, we also know that Zachary had 45 more postcards than John. So we can set up an equation: 9x = 4x + 45. Let's solve this!

9x - 4x = 45
5x = 45
x = 9

So, Zachary initially had 9x postcards, which is 9 * 9 = 81 postcards. Ta-da!

(B) Now it's time to calculate how many postcards Zachary gave to John! We're given that after giving some postcards to John, Zachary had 6/7 as many postcards as John. Let's use our clown math skills again.

After giving away some postcards, Zachary has 6/7 as many postcards as John. So Zachary now has (6/7) * 4x postcards.

But we know that Zachary initially had 9x postcards, so we can set up another equation: (6/7) * 4x = 9x.

Let's solve this equation one more time, just for fun!

(6/7) * 4x = 9x
Multiply both sides by 7: 6 * 4x = 63x
24x = 63x
63x - 24x = 0
39x = 0

Oops, sorry! It seems I made a boo-boo here. There doesn't seem to be a solution to this equation, which means I need to go back and check my calculations.